ZO-1 Regulates Intercalated Disc Composition and Atrioventricular Node Conduction. Issue 2 (3rd July 2020) - Dai, Wenli; Nadadur, Rangarajan D.; Brennan, Jaclyn A.; Smith, Heather L.; Shen, Kaitlyn M.; Gadek, Margaret; Laforest, Brigitte; Wang, Mingyi; Gemel, Joanna; Li, Ye; Zhang, Jing; Ziman, Bruce D.; et al.
Abstract : Rationale: ZO-1 (Zona occludens 1), encoded by the tight junction protein 1 ( TJP1 ) gene, is a regulator of paracellular permeability in epithelia and endothelia. ZO-1 interacts with the actin cytoskeleton, gap, and adherens junction proteins and localizes to intercalated discs in cardiomyocytes. However, the contribution of ZO-1 to cardiac physiology remains poorly defined. Objective: We aim to determine the role of ZO-1 in cardiac function. Methods and Results: Inducible cardiomyocyte-specific Tjp1 deletion mice ( Tjp1 fl/fl ; Myh6 Cre/Esr1* ) were generated by crossing the Tjp1 floxed mice and Myh6 Cre/Esr1* transgenic mice. Tamoxifen-induced loss of ZO-1 led to atrioventricular (AV) block without changes in heart rate, as measured by ECG and ex vivo optical mapping. Mice with tamoxifen-induced conduction system-specific deletion of Tjp1 ( Tjp1 fl/fl ; Hcn4 CreERt2 ) developed AV block while tamoxifen-induced conduction system deletion of Tjp1 distal to the AV node ( Tjp1 fl/fl ; Kcne1 CreERt2 ) did not demonstrate conduction defects. Western blot and immunostaining analyses of AV nodes showed that ZO-1 loss decreased Cx (connexin) 40 expression and intercalated disc localization. Consistent with the mouse model study, immunohistochemical staining showed that ZO-1 is abundantly expressed in the human AV node and colocalizes with Cx40. Ventricular conduction was not altered despite decreased localization of ZO-1 and Cx43 at the ventricular intercalated disc and modestly decreased left ventricular ejection fraction, suggesting ZO-1 is differentially required for AV node and ventricular conduction. Conclusions: ZO-1 is a key protein responsible for maintaining appropriate AV node conduction through maintaining gap junction protein localization. Abstract : Supplemental Digital Content is available in the text.